BAD guidelines for the management of HS (acne inversa) 2018. (1st May 2019) - Ingram, J.R.; Collier, F.; Brown, D.; Burton, T.; Burton, J.; Chin, M.F.; Desai, N.; Goodacre, T.E.E.; Piguet, V.; Pink, A.E.; Exton, L.S.; Mohd Mustapa, M.F.
Summary: Hidradenitis suppurativa (HS) is a long‐term skin condition causing multiple boils in skin creases such as the arm pits and groins. The boils are painful and produce pus, and permanent scarring occurs as the disease progresses. As a result, it has a large impact on quality of life. HS affects about 1 in 100 of the UK population and it tends to start in early adulthood. The British Association of Dermatologists commissioned a HS guideline development group composed of information specialists, a HS patient and carer, and UK clinicians including dermatologists, a dermatology nurse, plastic surgeon and general practitioner (GP). The group, based in the UK, were asked to produce treatment recommendations based on a systematic review of the evidence. The evidence was converted to recommendations using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Nearly 3000 evidence records were identified through database searches. Initial recommendations for HS management by GPs and hospital clinics include to provide a patient information leaflet, record baseline disease severity, measure pain and treat if needed, measure quality of life, record a count of skin lesions, and provide wound dressings if required. Patients should be screened for cardiovascular disease risk factors as well as for depression and anxiety. Patients should also be offered smoking cessation and weight management referral if relevant. A treatment ladder of medical therapy is recommended, starting with oral tetracyclines, then the combination of clindamycin and rifampicin, acitretin in men and non‐fertile women, dapsone and progressing to adalimumab injections if required. Surgical treatment with wide removal and a range of closure methods is placed towards the end of the medical treatment pathway, reflecting current UK practice and a relative lack of evidence. Future research recommendations and audit criteria are included.